Beyond good and evil : prelude to a philosophy of the future - Nietzsche, Friedrich Wilhelm, 1844-1900 (Oxford world's classics (Oxford University Press), 1998)
"Always provocative, the Friedrich Nietzsche of Beyond Good and Evil (1886) is at once sceptical psychologist and philosopher-seer, passionately unmasking European society with his piercing insights and uncanny prescience. This masterpiece of his maturity considers quintessential Nietzschean topics such as the origins and nature of Judaeo-Christian morality; the end of philosophical dogmatism and beginnings of perspectivism; the questionable virtues of science and scholarship; liberal democracy, nationalism, and women's emancipation. Written in his most masterful style, full of irreverence and brio, this extraordinary book dissects self-deluding human behaviour, bankrupt intellectual traditions, and the symptoms of social decadence, while at the same time advancing an extra-moral wisdom to be shared by those kindred souls who think 'beyond good and evil'."--Jacket.